OCCURRENCE OF EXTENDED SPECTRUM BETA LACTAMASE PRODUCING KLEBSIELLA PNEUMONIAE ISOLATES IN A TERTIARY CARE HOSPITAL IN LALITPUR - Manandhar, Ruchee (Journal of Chitwan Medical College, 2024)
Background: Bacteria have been ever-evolving and conferring resistance to advanced and more powerful antibacterial drugs. With the increase in multidrug resistance and extended spectrum beta lactamase (ESBL) producing isolates worldwide, Nepal too faces diagnostic and therapeutic challenges. The dilemma to choose right empirical therapy leads to delayed and inappropriate treatment resulting in increased morbidity, mortality and increased hospital stay. The objective of our study was to determine the occurrence of ESBL producing Klebsiella pneumoniae (ESBLK) in clinical samples of patients attending KIST Medical College and Teaching Hospital (KISTMCTH) and determine their antimicrobial susceptibility pattern. Methods: A total of 212 clinical samples in which Klebsiella pneumoniae was isolated were studied. Isolates were identified by standard microbiological methods and tested for in vitro antibiotic susceptibility by modified Kirby-Bauer disc diffusion method. Phenotypic confirmatory disc diffusion test was performed for confirmation of ESBL production. The obtained data was entered and analyzed in WHONET 2023 program. Results: A total of 212 Klebsiella pneumoniae isolates were isolated in our study. Among these, 41 (19.33%) of K. pneumoniae were found to be ESBL producers. The ESBLK isolates were 100% sensitive to Colistin and Polymyxin B. Least sensitivity was seen against Ciprofloxacin and Cotrimoxazole. Meropenem resistance was seen in 26.8% ESBLK isolates. Conclusions: Our study shows increased prevalence of ESBLK resistant to commonly used antibiotics Therefore, judicious use of antimicrobials, active infection control practices, stringent antibiotic policy and regular surveillance should be conducted to keep antibiotic resistance at bay.